Simulasi Pola Tanam (Palawija) Berdasarkan Potensi Ketersediaan Air di Kampung Kweel Distrik Elikobel, Kabupaten Merauke - Yosehi Mekiuw; Wahida Wahida (Musamus AE Featuring Journal, 2018)
Agriculture is one of the sectors that play a role in deciding the rural poverty chain. Agriculture is a productive sector for rural communities in increasing household incomes through cultivation of crops and livestock. The purpose of this study is to plan, establish or simulate appropriate planting pattern based on the potential availability of water resources and land, so that the production or productivity of plants and land can be obtained optimally and can improve the rural economy. The method used in this research is descriptive analytic method. Based on the results obtained that the potential of available water resources in Kampung Kweel is able to be used as an irrigation water source in both monoculture and polyculture (tumpangsari).